2018
DOI: 10.1029/2017jd028242
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Organic Aerosol Formation From Isoprene Epoxides in the Pearl River Delta, South China: IEPOX‐ and HMML‐Derived Tracers

Abstract: Atmospheric photooxidation of isoprene forms isoprene epoxydiols (IEPOX) and hydroxymethel-methyl-α-lactone (HMML) via hydroperoxyl radical (HO 2 ) channel and NO/NO 2 channel, respectively. Reactive uptake of these epoxides onto particles produces isoprene secondary organic aerosols (iSOA). Currently, there is little information regarding these two epoxides during iSOA formation in polluted regions. In this study, iSOA tracers from IEPOX and HMML were measured from summer to fall in the heavily polluted Pearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 98 publications
2
37
2
Order By: Relevance
“…These values are within the range of 2-MG-OS measured in other urban locations (Nguyen et al, 2014;Rattanavaraha et al, 2016;Hettiyadura et al, 2019). However these concentrations are considerably higher than previously observed at two Chinese polluted regional sites 445 (Wang et al, 2018;He et al, 2018). At these locations, the ratio of the low-NO to high-NO isoprene OS tracer average concentrations was close to 1.5 (2-MT-OS:2-MG-OS; Beijing = 1.47, Wanqingsha = 1.57).…”
Section: -Methyl Glyceric Acid Os (2-mg-os)contrasting
confidence: 54%
See 2 more Smart Citations
“…These values are within the range of 2-MG-OS measured in other urban locations (Nguyen et al, 2014;Rattanavaraha et al, 2016;Hettiyadura et al, 2019). However these concentrations are considerably higher than previously observed at two Chinese polluted regional sites 445 (Wang et al, 2018;He et al, 2018). At these locations, the ratio of the low-NO to high-NO isoprene OS tracer average concentrations was close to 1.5 (2-MT-OS:2-MG-OS; Beijing = 1.47, Wanqingsha = 1.57).…”
Section: -Methyl Glyceric Acid Os (2-mg-os)contrasting
confidence: 54%
“…Hettiyadura et al, 2019) but are higher than summer time observations at polluted regional background sites in China (Wang et al, 2018;He et al, 2018). The lower amounts of IEPOX-derived SOA results in an average AMS fC5H6O in Beijing during the APHH project of only 0.2 %, similar to observations in 390 other urban studies (Hu et al, 2015).…”
Section: -Methyltetrol Os (2-mt-os)mentioning
confidence: 54%
See 1 more Smart Citation
“…However, organic compounds and inorganic salts often coexist with varying concentrations in the atmosphere. For instance, field studies have reported that the mass concentration of 2methyltetrols ranges from 1 to over 100 ng m −3 , while that of AS ranges from few to tens of micrograms per cubic meter (Schauer et al, 2002;Lewandowski et al, 2007;Kleindienst et al, 2010;Budisulistiorini et al, 2013;Xu et al, 2014;Hu et al, 2015). The mass concentration ratio of sulfate-to-2methyltetrols can vary greatly from ∼ 1.89 to ∼ 250.…”
Section: Introductionmentioning
confidence: 99%
“…1b). Hofzumahaus et al (2009) observed extremely high OH concentrations in the PRD and proposed a recycling mechanism that increases the stability of OH in the air of polluted regions. All of the abovementioned results indicate a high atmospheric oxidative capacity in the PRD, as O 3 , NO x , and OH are intimately linked in atmospheric chemistry.…”
Section: Introductionmentioning
confidence: 99%